Proposal for a program to enhance renal transplantation opportunity for highly sensitized patients - Campos, Érika Fernandes (2010)
Purpose: The accumulation of highly sensitized patients (HSP) on renal transplant waiting lists is a universal problem and finding donors for them represents a major challenge for organ distribution organizations. The purpose of this report is to describe a possible Brazilian version of the Eurotransplant Acceptable Mismatch program and the results of a study performed to test its efficiency. Method: The acceptable mismatches were defined with the single antigen beads Luminex assay, each test being individually interpreted with aid of the HLAMatchmaker algorithm. Negative-crossmatch prediction was validated in 86 T cell crossmatches using complement dependent cytotoxicity with anti-human globulin. Results: The estimation of the chances of 40 HSP to find a donor through the program showed that about 70% of them would be offered an ABO compatible, zero HLA-DR mismatched, T and B cell crossmatch negative graft within a two-year period after joining the program. On the other hand, for about 30% of the patients, the chances to find a suitable donor would be minimal, even after three or five years. Conclusions: We estimated that around 70% of the HSP would clearly benefit from the algorithm proposed in this study. On the other hand, those patients for whom it would be highly improbable to find a compatible donor would be primary candidates for desensitization/antibody reduction protocols. Therefore, we concluded that the information regarding the transplantability of each HSP provided by the algorithm herein described is a powerful tool for a proper management of highly sensitized patients in regional, national and international organizations as to deceased donor kidneys distribution.